KRITIK TERHADAP SISTEM EKONOMISOSIALIS DAN KAPITALIS - M. Sholahuddin (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2001)
The failure of economic capitalism system stated by Adam Smith (1723-1790) and David Ricardo (1772-1823) actually have been criticized by Karl Marx (1818-1883) in his book "A Contribution to the Critique of Political Economy" (1857) and "A Contribution to the Critique of Political Economy" (1859). Karl Marx and Engels compile a new synthesis of economic socialist system. Stranger enough, socialism particularly as economic ideology is destroyed earlier than Capitalism. Meanwhile, capitalism still survives by transforming performance. For examples, at the time of the glory of Socialism age, capitalism was transformed into socialism state with social justice and welfare state concepts, and when Islam began to rise, it was transformed into new performance as if it has characteristic of Islam, but in fact it is still capitalism. This writing tries to criticize both of them by Islamic economic perspective.